Book review: Zelenkauskaitė, Asta. Creating chaos online: disinformation and subverted post-publics - Elena Maceviciute (Information Research: An International Electronic Journal)
Zelenkauskaitė, Asta. Creating chaos online: disinformation and subverted post-publics. Ann Arbor, MI: University of Michigan Press, 2022. vii, 310 p. ISBN 978-0-472-05552-4